1999
DOI: 10.1002/(sici)1097-0215(19990924)83:1<50::aid-ijc10>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus genomes are found predominantly in IgA-positive B cells in the blood of healthy carriers

Abstract: B lymphocytes have been identified as the main reservoir of latent Epstein‐Barr virus (EBV) in healthy virus carriers. We have established a semi‐quantitative PCR method to estimate the EBV genome load in the blood B‐cell subpopulation in healthy individuals. EBV DNA was detected in subfractionated IgM‐, IgG‐ and IgA‐positive B cells. Between 80% and 90% of the viral DNA was found in the IgA‐positive compared with the IgA‐negative fraction. Int. J. Cancer 83:50–54, 1999. © 1999 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
3
16
1
Order By: Relevance
“…This fact suggests that if EBV uses tonsillar memory B cells as a direct target, the virus preferentially accesses isotype-switched cells. In agreement with our observations, the vast majority of EBV DNA in peripheral blood cells from EBV carriers has been detected in surface-IgA-positive B cells (12). Moreover, recent work on peripheral blood B cells isolated from patients with infectious mononucleosis found that EBV-infected cells were preferentially excluded from the IgM isotype in the CD27 ϩ memory B-cell pool (36).…”
Section: Discussionsupporting
confidence: 91%
“…This fact suggests that if EBV uses tonsillar memory B cells as a direct target, the virus preferentially accesses isotype-switched cells. In agreement with our observations, the vast majority of EBV DNA in peripheral blood cells from EBV carriers has been detected in surface-IgA-positive B cells (12). Moreover, recent work on peripheral blood B cells isolated from patients with infectious mononucleosis found that EBV-infected cells were preferentially excluded from the IgM isotype in the CD27 ϩ memory B-cell pool (36).…”
Section: Discussionsupporting
confidence: 91%
“…Careful quantitation of the total number of genomes before and after fractionation would reveal whether a true enrichment in IgA ϩ cell was occurring. Such an enrichment was not seen in either our or the previously published studies (35).…”
Section: Ebv Is Present In Both Cd5 ϫ (B2) and Cd5 ϩ (B1) B Cells In contrasting
confidence: 80%
“…A recent report claimed that EBV in the peripheral blood was restricted to IgA-positive cells (35). However, in several studies, we have failed to repeat these observations.…”
Section: Ebv Is Present In Both Cd5 ϫ (B2) and Cd5 ϩ (B1) B Cells In mentioning
confidence: 62%
See 2 more Smart Citations